Control of ITCZ Width by Low‐Level Radiative Heating From Upper‐Level Clouds in Aquaplanet Simulations. Issue 11 (13th June 2018) - Dixit, Vishal; Geoffroy, Olivier; Sherwood, Steven C.
Abstract: Atmospheric cloud radiative effects (ACRE) narrow the Intertropical Convergence Zones (ITCZs) in climate models. Some studies have attributed this to the upper tropospheric heating by deep clouds. We report two types of idealized aquaplanet experiments, one where ACRE in specific altitude ranges is removed and another where the ACRE associated with clouds in specific altitude ranges is removed. Lower tropospheric heating due to upper tropospheric clouds in the deep tropics exerts the greatest impact on the ITCZ width and meridional overturning, even though the heating is weaker than in the upper troposphere. It is argued that this is because radiatively driven changes in the shallow circulation drive a feedback via net import of MSE and make the ITCZ more unstable in its core, thereby forcing the ITCZ to contract. The radiative effects of clouds in the subsiding subtropics are found to be of secondary importance in driving the necessary circulation changes. Plain Language Summary: The climate models do not simulate the latitudinal extent ( the width ) of the tropical oceanic rainbands, that is, the Intertropical Convergence Zones (ITCZs), accurately. This problem has been identified as a fundamental puzzle of climate science and is one of the major focus of WCRP's‐Clouds, circulation and climate sensitivity project. Recent studies demonstrated that the cloud radiative heating effects reduce the ITCZ width. In this paper, we perform idealized experiments to identify the relative roles of upper versus lower and local versus remote clouds in changing ITCZ width. In our experiments, we either artificially alter the radiative heating of all clouds in specific atmospheric layers or alter the heating due to clouds in specific atmospheric layers. We found that the lower‐level heating due to upper‐level clouds within the ITCZ affects the lower‐level overturning circulation and hence the ITCZ width the most. The lower‐level overturning strengthens the moisture import in the ITCZ core and enhances the precipitation there. In response, the precipitation on the edges decreases and the ITCZ width reduces. The clouds remote to the ITCZ do not alter the ITCZ width significantly. Key Points: Lower tropospheric heating by upper tropospheric clouds is the dominant cloud radiative influence on the location of the ITCZ Local radiative effects inside ITCZ are more effective than remote effects Shallow circulations mediate the changes in ITCZ width